Predictors of noninstitutionalized survival 1 year after hip fracture: A prospective observational study to develop the Marburg Rehabilitation Tool for Hip fractures (MaRTHi). Issue 37 (September 2017) - Buecking, Benjamin; Eschbach, Daphne; Knobe, Matthias; Oberkircher, Ludwig; Balzer-Geldsetzer, Monika; Dodel, Richard; Sielski, Robert; Doering, Bettina; Ruchholtz, Steffen; Bliemel, Christopher
Abstract : Abstract: Hip fractures are frequent fractures in geriatric patients. These fractures have great socioeconomic implications because of the significantly higher risk of mortality and institutionalization. The aim of this study was to develop a prognostic tool to predict survival without institutionalization within 1 year after hip fracture. A total of 402 hip fracture patients aged >60 years (84% community-dwelling) were included in a prospective observational cohort study. Multiple regression analyses determined independent predictors for noninstitutionalized 1-year survival. Finally, the Marburg Rehabilitation Tool for Hip fractures (MaRTHi) was developed based on these independent predictors. Of the 312 patients who were followed up for 1 year, 168 (54%) survived noninstitutionalized, 104 (33%) died, and 40 (13%) lived in nursing homes. Independent predictors for patients' noninstitutionalized survival included the American Society of Anesthesiologists (ASA) score [ASA 1 or 2: odds ratio (OR) = 7.828; 95% confidence interval (CI) = 2.496–24.555 and ASA 3: OR = 8.098; 95% CI = 2.982–21.993 compared with ASA 4 or 5], the Mini Mental State Examination upon admission to the hospital (OR = 7.365; 95% CI = 2.967–18.282 for 27–30 compared with 0–10), patients' age (OR = 2.814; 95% CI = 1.386–5.712 for 75–89 y and OR = 2.520; 95% CI = 0.984–6.453 for 90–99 y compared with 60–74 ys), and prefracture EQ-5D (OR = 2.163; 95% CI = 1.119–4.179 for EQ-5D >0.80 compared with <0.60). The area under the receiver-operating characteristic curve was 0.756 (95% CI = 0.703–0.809), and the sensitivity analysis yielded a MaRTHi score that ranged from 0 to 12 points. The MaRTHi score is the first instrument to predict noninstitutionalized survival with only 4 variables. In addition to 3 well-known factors influencing outcome (age, comorbidities, and cognitive ability), prefracture health-related quality of life was identified as an independent predictor of noninstitutionalized survival. Further studies must be conducted to validate the MaRTHi score and define cutoff scores. Health-related quality of life seems to be an important patient-reported outcome measurement and may play a role in determining patient prognosis.